2002
DOI: 10.1159/000058424
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Bony Septum: A Split Cord Malformation Variant

Abstract: Split cord malformations (SCMs) are rare spinal anomalies and their classification is still a matter of debate. There is no widespread consensus on the embryological basis of this entity. The unified theory, proposed by Pang et al. [Neurosurgery 1992;31:451–480], was an attempt to explain the embryogenetic mechanism as a basic error occurring around the time when the primitive neuroenteric canal closes. We report two unusual cases of SCMs with a dorsally situated bony spur. We analyzed the radiological, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…He considered the dorsal bony spur as one of the vertebral anomalies involving the lamina, although he did not give any persuading explanations why. Kamil-Melih et al [7] detected a bony spur situated dorsally with two hemicords in a single dural sac, just like the atypical type II SCM reported in this article. Katoh et al [8] also reported a case of type II SCM without a fibrous septum which could not be explained by the unified theory either.…”
Section: Discussionsupporting
confidence: 66%
“…He considered the dorsal bony spur as one of the vertebral anomalies involving the lamina, although he did not give any persuading explanations why. Kamil-Melih et al [7] detected a bony spur situated dorsally with two hemicords in a single dural sac, just like the atypical type II SCM reported in this article. Katoh et al [8] also reported a case of type II SCM without a fibrous septum which could not be explained by the unified theory either.…”
Section: Discussionsupporting
confidence: 66%
“…[1][2][3][4]7 The presence of congenital skin abnormalities on the back may be associated with a serious underlying spinal anomaly. 8 All of our patients with SCM had skin abnormalities in the lumbosacral region.…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous changes that may overly an SCM have been previously reported, including hypertrichosis, dysplastic skin, dermal sinus tract, subcutaneous lipoma, capillary hemangioma, vascular nevi and hyperpigmentation. [1][2][3][4][5][6][7] Recognizing these skin lesions can guide the physician to an underlying SCM.…”
Section: Introductionmentioning
confidence: 99%
“…Individual case reports of nine such cases have been reported in the English literature. [25] The authors report four cases of SCMs with a dorsally located bony spur and the pertinent literature is reviewed.…”
Section: Introductionmentioning
confidence: 99%